Comparison of a guaiac based and an immunochemical faecal occult blood test in screening for colorectal cancer in a general average risk population. Issue 2 (4th August 2006) - Guittet, L; Bouvier, V; Mariotte, N; Vallee, J P; Arsène, D; Boutreux, S; Tichet, J; Launoy, G
Abstract : Background: The guaiac faecal occult blood test (G-FOBT) is recommended as a screening test for colorectal cancer but its low sensitivity has prevented its use throughout the world. Methods: We compared the performances of the reference G-FOBT (non-rehydrated Hemoccult II test) and the immunochemical faecal occult blood test (I-FOBT) using different positivity cut-off values in an average risk population sample of 10 673 patients who completed the two tests. Patients with at least one test positive were asked to undergo colonoscopy. Results: Using the usual cut-off point of 20 ng/ml haemoglobin, the gain in sensitivity associated with the use of I-FOBT (50% increase for cancer and 256% increase for high risk adenoma) was balanced by a decrease in specificity. The number of extra false positive results associated with the detection of one extra advanced neoplasia (cancer or high risk adenoma) was 2.17 (95% confidence interval 1.65–2.85). With a threshold of 50 ng/ml, I-FOBT detected more than twice as many advanced neoplasias as the G-FOBT (ratio of sensitivity = 2.33) without any loss in specificity (ratio of false positive rate = 0.99). With a threshold of 75 ng/ml, associated with a similar positivity rate to G-FOBT (2.4%), the use of I-FOBT allowed a gain in sensitivity of 90% and a decrease in the false positive rate of 33% for advanced neoplasia. Conclusions: Evidence in favour of the substitution of G-FOBT by I-FOBT is increasing, the gain being more important for high risk adenomas than for cancers. The automated reading technology allows choice of the positivity rate associated with an ideal balance between sensitivity and specificity.